Pengaruh Konten Review, Promosi Digital, Dan Persepsi Harga Di Tiktok Terhadap Keputusan Pembelian Produk OMG Beauty - Zahra Nur Annisa; Sofyan Lazuardi; Asmirin Noor (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of review content, digital promotion, and price perception on TikTok toward purchasing decisions of OMG Beauty products in Sidoarjo. The research method used is descriptive and verificative quantitative with purposive sampling technique. The population in this study consists of TikTok users in Sidoarjo who have purchased OMG Beauty products, with a sample of 100 respondents obtained using the Taro Yamane formula. Data were collected using an online questionnaire and analyzed with multiple linear regression with the equation Y=2,134+0,312X1​+0,276X2​+0,198X3​​, where Y represents purchasing decisions, X1 represents review content, X2 represents digital promotion, and X3 represents price perception. The results show that review content, digital promotion, and price perception have a positive and significant effect on purchasing decisions both partially and simultaneously, with t values of 4.821, 3.721, and 4.215 respectively (p < 0.05), and an F value of 57.283 (p = 0.000). The coefficient of determination (R²) of 0.65 indicates that 65% of the variation in purchasing decisions is explained by these three variables. The classical assumption tests show that the data are normally distributed (Kolmogorov-Smirnov sig = 0.200), there is no multicollinearity (VIF < 10), and no heteroscedasticity. This study confirms that review content is the most dominant factor influencing consumer purchasing decisions on TikTok.